Lifestyle changes and risk of tuberculosis in patients with type 2 diabetes mellitus: A nationwide cohort study - Park, Jiho; Yoon, Ji Hyun; Ki, Hyun Kyun; Han, Kyungdo; Kim, Hyungjin (Frontiers in Endocrinology, 2022)
We investigated the impacts of lifestyle changes, namely smoking, alcohol intake, and exercise on the development of tuberculosis (TB) in patients with type 2 diabetes mellitus (T2DM). A retrospective population-based cohort study used data from Korean National Health Insurance system database. We examined subjects diagnosed with T2DM and without previous history of TB between 2009 and 2012 who underwent 2 serial health examinations. The study participants were classified into each four groups based on changes in the patterns of smoking, alcohol intake and exercise at the time of second examination. The outcome of the study was newly diagnosed TB in patients with T2DM. Among 1,659,804 included subjects, TB was newly diagnosed with 10,288 subjects. Both consistent smokers (HR 1.406; 95% CI 1.333-1.483) and new smokers (HR 1.185; 95% CI 1.063-1.320) had a higher TB risk than smoking quitter (HR 1.107; 95% CI 1.009-1.216) and never smokers. Both consistent heavy drinkers (HR 1.281; 95% CI 1.172-1.399) and heavy drinking quitters (HR 1.247; 95% CI 1.147-1.356) had a higher TB risk than new heavy drinkers and never drinkers. With respect to exercise, persistent non-exercisers (HR 1.309; 95% CI 1.72-1.399) and exercise quitters (HR 1.164; 95% CI 1.066-1.271) had a higher TB risk than new exercisers. In the subgroup analysis, a significant interaction was observed between lifestyle changes and age. We found that lifestyle changes were associated with development of TB in patients with T2DM. These results suggest that lifestyle management could be a valuable strategy for control of TB in Korea.